Effective viscosity and dynamics of spreading epithelia: a solvable model. Issue 6 (18th January 2017) - Blanch-Mercader, C.; Vincent, R.; Bazellières, E.; Serra-Picamal, X.; Trepat, X.; Casademunt, J.
Abstract : A solvable model that shows a broad range of applicabilities for the quantitative analysis and interpretation of force microscopy data of spreading monolayers. Abstract : Collective cell migration in spreading epithelia in controlled environments has become a landmark in our current understanding of fundamental biophysical processes in development, regeneration, wound healing or cancer. Epithelial monolayers are treated as thin layers of a viscous fluid that exert active traction forces on the substrate. The model is exactly solvable and shows a broad range of applicabilities for the quantitative analysis and interpretation of force microscopy data of monolayers from a variety of experiments and cell lines. In addition, the proposed model provides physical insights into how the biological regulation of the tissue is encoded in a reduced set of time-dependent physical parameters. In particular the temporal evolution of the effective viscosity entails a mechanosensitive regulation of adhesion. Besides, the observation of an effective elastic tensile modulus can be interpreted as an emergent phenomenon in an active fluid.